2019
DOI: 10.1055/s-0039-1687916
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Length of Stay after Microsurgical Breast Reconstruction with a Standardized Postoperative Protocol

Abstract: Background Despite widespread acceptance of enhanced recovery after surgery protocols in other surgical specialties, plastic surgery has been slow to adopt fast-track principles. Recently, however, studies have shown that patients undergoing microsurgical breast reconstruction may benefit from a comprehensive postoperative protocol. Methods All microsurgical breast reconstructions with abdominal free flaps performed by the senior author (A.K.) at a single institution from June 2009 to December 2013 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 111 publications
1
18
0
Order By: Relevance
“…ERAS protocols have demonstrated ability to standardize postoperative stays and facilitate discharge. [12][13][14][15][16][17] Our study has exhibited the influence of patient expectation of discharge. We have shown that setting an expectation of a particular early discharge date can significantly affect the LOS.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…ERAS protocols have demonstrated ability to standardize postoperative stays and facilitate discharge. [12][13][14][15][16][17] Our study has exhibited the influence of patient expectation of discharge. We have shown that setting an expectation of a particular early discharge date can significantly affect the LOS.…”
Section: Discussionmentioning
confidence: 87%
“…In this study, patients who were discharged earlier had a similar complication rates to those had a standard discharge and no patients had flap loss Several studies have analyzed ERAS protocols for microvascular breast reconstruction and have found decreased postoperative narcotic use and LOS. [12][13][14][15][16][17]29 Batdorf et al found that in their ERAS cohort of 49 individuals, they were able to reduce LOS from 5.5 to 3.9 days. 13 Astanehe et al similarly published a study on ERAS protocols for microvascular breast reconstruction, finding that the LOS for their ERAS cohort was 4.8 days, compared with their traditional cohort's LOS of 6.6 days.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies have analyzed the efficacy of various enhanced recovery after surgery (ERAS) protocols in microsurgical, DIEP, and alloplastic breast reconstruction cases. [28][29][30] This study aims to evaluate outcomes with this particular DIEP pathway to assess its safety and feasibility in clinical practice at a major academic medical center.…”
mentioning
confidence: 99%